Withaferin A and Ovarian Cancer Antagonistically Regulate Skeletal Muscle Mass - Straughn, Alex R.; Kelm, Natia Q.; Kakar, Sham S. (Frontiers in Cell and Developmental Biology, 2021)
Cachexia is a complex wasting syndrome that overwhelmingly affects the majority of late-stage cancer patients. Additionally, there are currently no efficacious therapeutic agents to treat the muscle atrophy induced by the cancer. While several preclinical studies have investigated the molecular signals orchestrating cachexia, very little information exists pertaining to ovarian cancer and the associated cachexia. Work from our lab has recently demonstrated that the steroidal lactone Withaferin A (WFA) is capable of attenuating the atrophying effects of ovarian cancer in a preclinical mouse model. However, it remained to be determined whether WFA’s effect was in response to its anti-tumorigenic properties, or if it was capable of targeting skeletal muscle directly. The purpose of this study was to uncover whether WFA was capable of regulating muscle mass under tumor-free and tumor-bearing conditions. Treatment with WFA led to an improvement in functional muscle strength and mass under tumor-bearing and naïve conditions. WFA and ovarian cancer were observed to act antagonistically upon critical skeletal muscle regulatory systems, notably myogenic progenitors and proteolytic degradation pathways. Our results demonstrated for the first time that, while WFA has anti-tumorigenic properties, it also exerts hypertrophying effects on skeletal muscle mass, suggesting that it could be an anti-cachectic agent in the settings of ovarian cancer.